Effect of cognitive stimulation based on puzzle games on learning achievement in school-aged stunted children - N, Nurjannah; T, Taamu; D, Dali; Noviawati Setya Arum, Dyah (Asian Journal of Pharmaceutical Research and Development, 2023)
Introduction; Stunting causes obstacles to physical development but also threatens cognitive development which has an impact on reducing children's productivity in adulthood. So efforts are needed to helpth ecognitive development of stunting children through educational games. Objective; Effect of Puzzle Game-Based Cognitive Stimulation on Learning Achievement of Stunted Children of School Age. Method; This type of pre-experimental research with a one group pre test-post test design. This study used measurements three times before the intervention and three times after the intervention. A sample of 36 people with the criteria of a stunted child based on BMI results according to measurements of height/age and weight/age. Results; the average value of stunting children's learning achievement given cognitive stimulation based on a puzzle game is PreTest 1 = 70.36, Post Test 1 = 69.36; Pre Test 2 = 72.36, Post Test 2 = 69.36, and PreTest 3 = 74.63, Post Test 3 = 70.72. In the statistical test results with the paired T-Test, there is a statistically significant difference (p <0.05) significant for all puzzle game interventions given to stunting children. Suggestion; the need for cognitive stimulus-based learning methods through puzzle games, as a learning approach technique for elementary school-age children who are stunted.